Optimalisasi Aplikasi SIP sebagai Sarana Penyelenggaraanujian di SMA Negeri 1 Pangandaran - Annisa Kania Fauzani Tarigan; Hani Pitriani; Acep Ridwan Maulana (J-STAF : Siddiq, Tabligh, Amanah, Fathonah, 2023)
The exam is one way to evaluate the learning process and is a means to measure students' abilities in a field of study. Initially, exams and learning were carried out conventionally, but over time and the implementation of the independent curriculum, exams and learning at SMAN 1 Pangandaran are now using gadgets to support the learning process. Based on these conditions, the school created an online learning and examination system that students and teachers could access in the form of a Google form. Learning runs smoothly but is often constrained by the network due to the large number of blank spot areas at SMAN 1 Pangandaran. Because of this situation, the school created a semi-online exam system application, namely the SIUS application, which is a local school application. The method used in this research is a qualitative descriptive approach. The technique in this study is the method of observation, interviews and documentation related to the management of the learning system and exams at SMAN 1 PANGANDARAN. The object of this study is to analyze the effectiveness of using the SIUS application in learning and exams at SMAN 1 PANGANDARAN. The results of the study show that the creation and use of the SIUS application is very effective in supporting student learning. Management of exam data for students and teachers is easier because it is automatically managed by the SIUS application. This application has had a significant impact on the teaching and learning process.